Implementation of respiratory‐gated VMAT on a Versa HD linear accelerator. (18th August 2017) - Snyder, Jeffrey E.; Flynn, Ryan T.; Hyer, Daniel E.
Abstract: The accurate delivery of respiratory‐gated volumetric modulated arc therapy (VMAT) treatment plans presents a challenge since the gantry rotation and collimator leaves must be repeatedly stopped and set into motion during each breathing cycle. In this study, we present the commissioning process for an Anzai gating system (AZ‐733VI) on an Elekta Versa HD linear accelerator and make recommendations for successful clinical implementation. The commissioning tests include central axis dose consistency, profile consistency, gating beam‐on/off delay, and comparison of gated versus nongated gamma pass rates for patient‐specific quality assurance using four clinically commissioned photon energies: 6 MV, 6 FFF, 10 MV, and 10 FFF. The central axis dose constancy between gated and nongated deliveries was within 0.6% for all energies and the analysis of open field profiles for gated and nongated deliveries showed an agreement of 97.8% or greater when evaluated with a percent difference criteria of 1%. The measurement of the beam‐on/off delay was done by evaluating images of a moving ball‐bearing phantom triggered by the gating system and average beam‐on delays of 0.22–0.29 s were observed. No measurable beam‐off delay was present. Measurements of gated VMAT dose distributions resulted in decrements as high as 9% in the gamma passing rate as compared to nongated deliveries when evaluated against the planned dose distribution at 3%/3 mm. By decreasing the dose rate, which decreases the gantry speed during gated delivery, the gamma passing rates of gated and nongated treatments can be made equivalent. We present an empirically derived formula to limit the maximum dose rate during VMAT deliveries and show that by implementing a reduced dose rate, a gamma passing rate of greater than 95% (3%/3 mm) was obtained for all plan measurements.